PERANCANGAN DAN PEMBUATAN SISTEM KENDALI KIPAS ANGIN OTOMATIS BERBASIS MIKROKONTROLER ATMEGA 32 - Anggi Anugrah; Putra Jaya (Universitas Negeri Padang, 2019)
The design and manufacture of this tool aims to create a fan control system that can detect human presence, and regulate fan air circulation automatically towards the user. The method applied is atmega32 microcontroller which processes input in the form of a PIR sensor. The output component uses a relay to turn on the AC motor, the servo motor to direct the air circulation flow and the 16x2 LCD as a monitor of the fan process. The results of this final project aim to make it easier for humans to operate and control the direction of circulation of fan air flow automatically. Save electricity usage in economic terms because fans only operate when there are users.Keywords: Sensor PIR, Microcontroller, Motor Servo, LCD 16x2.